Study the IL-10 serum level in acute myeloid leukemia patients before &after chemotherapy - et.al, T.A-A. Hussain (Al-Qadisiyah Journal of Pure Science, 2017)
Interleukin-10 (IL-10) is commonly regarded as an anti-inflammatory. has pleiotropic effects in immunoregulation and inflammation and influences many aspects of the immune response ,and is cytokine that stimulates various hematopoietic cells,. and is primarily produced by monocytes and, to a lesser extent, lymphocytes, namely type 2 T helper cells (TH2), mastocytes, regulatory T cells.The function of IL-10 has been detected in the leukemic cells of most ALL and AML cases and it suppresses the immune reactions. The aim of this study to evaluate serum IL-10 concentration of patients before and after treatment ,and comparative with control subjects . The other aims is to associate this protein with age groups stage and the gender . A direct ELISA was used to quantify serum IL-10 concentrations in 60 patients with acute myeloid leukemia (AML)and 15 healthy subjects (control) ,and so there was significant effect of age on the level of IL_10 at AML patients,where no significant effect of gender on the level of IL_10. We found serum concentrations of IL-10 were significant decrease in patients with AML after treatment in compared with patients before treatment (P< 0.5) .